2015
DOI: 10.1038/ncb3241
|View full text |Cite|
|
Sign up to set email alerts
|

Complementary activities of TPX2 and chTOG constitute an efficient importin-regulated microtubule nucleation module

Abstract: Spindle assembly and function require precise control of microtubule nucleation and dynamics. The chromatin-driven spindle assembly pathway exerts such control locally in the vicinity of chromosomes. One of the key targets of this pathway is TPX2. The molecular mechanism of how TPX2 stimulates microtubule nucleation is not understood. Using microscopy-based dynamic in vitro reconstitution assays with purified proteins, we find that human TPX2 directly stabilises growing microtubule ends and stimulates microtub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
251
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(278 citation statements)
references
References 67 publications
27
251
0
Order By: Relevance
“…Untagged EB1 was expressed and purified as described (Roostalu et al , 2015). The final protein concentration was 1.2 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Untagged EB1 was expressed and purified as described (Roostalu et al , 2015). The final protein concentration was 1.2 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were imaged at 30°C on a TIRF microscope (iMIC, FEI Munich) described in detail previously (Duellberg et al , 2014; Maurer et al , 2014; Roostalu et al , 2015). Image acquisition and channel alignment were carried out as explained previously (Maurer et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D) is that TPX2 reduces the effective tubulin concentration in solution by sequestering free tubulin into multi-subunit complexes (Gruss et al, 2002;Roostalu et al, 2015;Scrofani et al, 2015). If this is the case, suppressed tubulin subunit on-rates could be an indirect consequence of enhanced formation of tubulin-TPX2 nucleation complexes (Fygenson et al, 1995;Schek et al, 2007;Scrofani et al, 2015).…”
Section: Tpx2 Slows Tubulin Subunit Off-rates During Microtubule Assementioning
confidence: 99%
“…Thus, TPX2 functions in part as a scaffold to bring mitotic regulators to spindle microtubules. Recent in vitro studies have demonstrated that TPX2 can promote the nucleation of microtubules in vitro (Roostalu et al, 2015;Wieczorek et al, 2015); however, the molecular mechanism by which this is accomplished remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%